CHALLENGES AND OPPORTUNITIES IN REVERSE LOGISTICS OF ELECTRONIC PRODUCTS - da Costa, Gentil Marciano (Revista Sistemática, 2020)
The reverse logistics of electronic products, or e-waste, presents significant challenges and opportunities in today’s global supply chain and environmental management contexts. Rapid technological innovation and shortened product lifespans have exponentially increased e-waste volumes, demanding efficient, sustainable reverse logistics systems. Challenges include regulatory fragmentation, material complexity, high costs, and consumer reluctance to participate in proper disposal. However, opportunities arise from recovering valuable materials, adopting advanced recycling technologies, and integrating circular economy principles. Successful reverse logistics implementation can enhance corporate sustainability, foster innovation in product design, and improve environmental outcomes. Social and economic factors, such as the role of informal recycling sectors and consumer education, also critically influence system effectiveness. Coordinated multi-stakeholder efforts and continuous technological advancements will be essential to transform e-waste from an environmental liability into a valuable resource.